EXPLORATION OF EFL TEACHERS’ EXPERIENCE TOWARD THE IMPLEMENTATION OF E-LEARNING AMIDST THE COVID-19 PANDEMIC: A QUALITATIVE INTERVIEW STUDY - Lee Getsemanita Karaeng; Debora Catherin Simanjuntak (IKIP Siliwangi, 2021)
This ongoing pandemic has demanded a rapid response to the unparalleled suspension of face-to-face teaching around the world. There has consequently been a growing interest in finding out how educators cope up with the transition. This study aims to explore the experience that EFL teachers in Jayapura encountered regarding the implementation of e-learning during the COVID-19 Pandemic. The data were collected through semi-structured interviews. A selection of 11 EFL teachers as the informants of this study was made based on the criteria of the study. By synthesizing the relevant literature with the collected data which were analyzed using thematic analysis, the findings were valued and wisely reviewed. The examination results of this study showed there are two emerging themes on teachers' experience in implementing e-learning, the themes are facilitating student learning and outcomes and self-regulated learning. Other themes that appeared were reviewed in terms of challenges, namely, obtaining interactive learning and teaching adjustment during transition. The findings can have important implications for ensuring the effective use of implementing e-learning toward English teaching.